2022
DOI: 10.1111/ijfs.15839
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid enhanced the emulsion stability, rheology and interface characteristics of Clanis Bilineata Tingtauica Mell protein stabilised oil‐in‐water emulsion

Abstract: Summary Clanis Bilineata Tingtauica Mell Protein (CBTMP) was one of the new natural insect protein resources. However, due to its strong surface hydrophobicity and poor emulsion stability, its application has greatly been limited. In this study, Pickering emulsions were prepared by CBTMP–Tannic acid (CBTMP–TA) particles and soybean oil (φ = 50%). The presence of TA significantly increased the zeta‐potential (from −23.5 ± 0.73 to −29.23 ± 0.58 mV) and three‐phase contact angle (from 129.9 ± 4.53° to 87.27 ± 3.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…However, some researchers have reported an increase in viscosity for emulsions prepared with polymers or proteins modified with TA. For instance, Wang et al 31 observed an increase in viscosity in oil−water emulsions of a TA-modified water-soluble insect protein as food emulsion systems. The authors attributed this behavior to covalent and noncovalent interactions between TA polyphenols and the protein.…”
Section: Resultsmentioning
confidence: 99%
“…However, some researchers have reported an increase in viscosity for emulsions prepared with polymers or proteins modified with TA. For instance, Wang et al 31 observed an increase in viscosity in oil−water emulsions of a TA-modified water-soluble insect protein as food emulsion systems. The authors attributed this behavior to covalent and noncovalent interactions between TA polyphenols and the protein.…”
Section: Resultsmentioning
confidence: 99%
“…The rheological properties of emulsion were measured by Haake Rheometer with a parallel steel plate geometry (Φ = 35 mm). The following scan modes were measured according to our previous methods ( 20 ):…”
Section: Methodsmentioning
confidence: 99%